1992
DOI: 10.1002/cjce.5450700428
|View full text |Cite
|
Sign up to set email alerts
|

Scrubbing of SO2 with trona solution in a spray drier

Abstract: Effect of operating variables on the scrubbing efficiency of SO2 in a spray drier was investigated using trona (Na2 CO3 · NaHCO3 · 2H2 O) solutions of different compositions. Results indicated that for a Na/S mole ratio of two (stoichiometric ratio) about 80% of the SO2 was removed. For higher Na/S ratios, SO2 removal efficiency increased by up to 100%. Increased SO2 concentration in the feed gas and decreased outlet temperature caused an increase in the overall conversion. At low temperatures and low SO2 conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 12 publications
1
6
0
Order By: Relevance
“…The presence of oxygen is clearly shown to slow down the overall reaction rate of SO 2 . This is likely due to the additional diffusional resistance in the transport of SO 2 to the reaction interface provided by the formation of Na 2 SO 4 . Owing to the occurrence of reaction , as mentioned before, the diffusion of oxygen toward the layer of solid products competes with the diffusion of SO 2 toward the reaction interface.…”
Section: Resultsmentioning
confidence: 88%
“…The presence of oxygen is clearly shown to slow down the overall reaction rate of SO 2 . This is likely due to the additional diffusional resistance in the transport of SO 2 to the reaction interface provided by the formation of Na 2 SO 4 . Owing to the occurrence of reaction , as mentioned before, the diffusion of oxygen toward the layer of solid products competes with the diffusion of SO 2 toward the reaction interface.…”
Section: Resultsmentioning
confidence: 88%
“…In limestone based scrubbing studies it is reported that the relative humidity should be over 70% [3]. The FGD studies using trona solution showed that 5% relative humidity is enough to remove the SO 2 with efficiency of 99% [15]. That means the reaction occurs at dry base.…”
Section: Mass Transfer and Reactionmentioning
confidence: 95%
“…Dogu et al reported that formation of Na 2 SO 4 causes an additional diffusion resistance for the transport of SO 2 to the reaction surface [15]. At low temperatures, formation of Na 2 S 2 O 5 was also expected during the reaction [16].…”
Section: Model Descriptionmentioning
confidence: 99%
“…A very typical example of such system is the spraying system in a pressuriser . The pressure‐swirl nozzle is an important type of nozzle, which is widely used in spray drying, scrubbing and combustion to obtain a large spraying field and small drop size. For its application in the pressuriser, the pressure‐swirl nozzle has an inevitable defect that the spray particles are not distributed uniformly in the container.…”
Section: Introductionmentioning
confidence: 99%